Contributing factors in learning programmable logic controller using path analysis - Masduki Zakarijah; Pramudi Utomo; Umi Rochayati; Mashoedah Mashoedah; Suprapto Suprapto; Arya sony (Jurnal Pendidikan Teknologi dan Kejuruan, 2023)
Learning Programmable Logic Controller (PLC) programming is influenced by several factors, that is: lecturer competence in PLC programming, adequacy of information technology infrastructure in learning, availability of learning media, vocational guidance procedures, and learning motivation. The purpose of this study: (a) to describe the factors that contribute to PLC programming learning, (b) to formulate a PLC programming competency model, and (c) to examine the determinants of PLC programming learning. Model testing method using Path Analysis.  The results of this analysis are expected to be able to describe the relational patterns between variables in learning PLC programming, as well as the direct and indirect impacts on the mastery of PLC programming competencies.  Keywords: PLC programming competency, path analysis, vocational education.